Comparison of Cox Proportional Hazards and Weibull Regression Models in Survival Analysis of Heart Failure Patients Using UCI Repository Data - Sianturi, Ardicha Appu; Hutapea, Risca Octaviyani; Sinaga, May Rani Tabitha (Lembaga Riset Mutiara Akbar, 2025)
Heart failure is a leading cause of death worldwide, with a high mortality rate due to decreased heart function and systemic complications. Survival analysis is used to understand factors that influence patient survival and estimate the risk of death based on clinical characteristics. This study aims to analyze factors that influence survival time in heart failure patients and compare the performance of the Cox Proportional Hazards (CoxPH) model with the Weibull Accelerated Failure Time (AFT) in predicting the risk of death. Data are from the Heart Failure Clinical Records Dataset (UCI Repository) which includes 299 patients with variables such as age, anemia, hypertension, serum creatinine levels, and ejection fraction. The analysis was performed using the Kaplan–Meier, CoxPH, and Weibull AFT methods with evaluation through AIC and C-index values. The results show that age, anemia, hypertension, and creatinine increase the risk of death, while ejection fraction is protective. The CoxPH model performed better (AIC 958.46; C-index 0.741) than the Weibull AFT (AIC 1282.24; C-index 0.259). Therefore, CoxPH is recommended for estimating relative risk between patients, while Weibull AFT is more suitable for estimating absolute survival duration.